Structural Features of the Central Labrador Trough: A Model for Strain Partitioning, Differential Exhumation and Late Normal Faulting in a Thrust Wedge under Oblique Shortening - Konstantinovskaya, Elena; Ivanov, Gennady; Feybesse, Jean-Louis; Lescuyer, Jean-Luc (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2019)
The west-verging fold and thrust belt of the Central Labrador Trough originated as a part of the New Quebec Orogen from rift inversion as a result of oblique collision and dextral transpression between the Archean Superior craton and the Archean block of the Core Zone during the Trans-Hudson orogeny (1.82−1.77 Ga). The structures associated with dextral transpression are well established in the northern segment of the orogen but not in the central part. We present new field structural observations along the ca. 70 km long W−E Minowean-Romanet transect that include not only elements of thrust tectonics but also previously undocumented examples of strike-slip shear zones and late brittle, semi-brittle and ductile extensional structures which occurred both in the frontal and rear parts of the thrust wedge. The newly described low-angle mineral lineation, axes of cylindrical folds and dextral mylonitic shear zones in the footwall of the Romanet Fault are oriented subparallel to the orogen and reflect the early phase of oblique convergence. Mineral lineations and striations on planes of normal faults in the hanging wall of the Romanet Fault are oriented orthogonal to the orogen and correspond to a later phase of exhumation driven by the combined effects of erosion and underplating. To explain the increase in the degree of exhumation along the orogen in the study area from NW to SE, we propose a model of strain partitioning and differential exhumation that resulted from longitudinal variations of shortening and erosion under an oblique convergence setting.